Thin low-gain avalanche detectors for particle therapy applications. (October 2020) - Vignati, A; Donetti, M; Fausti, F; Ferrero, M; Giordanengo, S; Hammad Ali, O; Martì Villarreal, O A; Mas Milian, F; Mazza, G; Monaco, V; Sacchi, R; Shakarami, Z; et al.
Abstract: The University of Torino (UniTO) and the National Institute for Nuclear Physics (INFN-TO) are investigating the use of Ultra Fast Silicon Detectors (UFSD) for beam monitoring in radiobiological experiments with therapeutic proton beams. The single particle identification approach of solid state detectors aims at increasing the sensitivity and reducing the response time of the conventional monitoring devices, based on gas detectors. Two prototype systems are being developed to count the number of beam particles and to measure the beam energy with time-of-flight (ToF) techniques. The clinically driven precision (< 1%) in the number of particles delivered and the uncertainty < 1 mm in the depth of penetration (range) in radiobiological experiments (up to 10 8 protons/s fluxes) are the goals to be pursued. The future translation into clinics would allow the implementation of faster and more accurate treatment modalities, nowadays prevented by the limits of state-of-the-art beam monitors. The experimental results performed with clinical proton beams at CNAO (Centro Nazionale di Adroterapia Oncologica, Pavia) and CPT (Centro di Protonterapia, Trento) showed a counting inefficiency <2% up to 100 MHz/cm 2, and a deviation of few hundreds of keV of measured beam energies with respect to nominal ones. The progresses of the project are reported.